The influence of trust and perceived playfulness on the relationship commitment of hospitality online social network-moderating effects of gender. Issue 5 (9th May 2016) - Li, Chi-Hua; Chang, Chun-Ming
Abstract : Purpose: From the commitment–trust theory angle, this study aims to understand why members of social network sites (SNSs) are willing to build a relationship commitment with hospitality SNSs, engage in online word-of-mouth (WOM) and show a willingness to repurchase. This paper proposes a model to express the relationship commitment and gender as a moderator in the relationship. Design/methodology/approach: The interviews of a formal survey were selected by a purposive sampling method, and an online questionnaire survey was conducted in Taiwan. This study used the partial least square method to conduct structural equation modeling analysis. Findings: The findings suggest that trust and perceived playfulness of the hospitality community have positive influences on relationship commitment, and also that the relationship commitment has a positive influence on online WOM and willingness to repurchase. This analysis provides strong support for the view that gender exerts a significant moderating role on our model relationships. Practical implications: SNSs aspiring to stand out in the highly competitive internet environment must cultivate consumers' trust and relationship commitment, and develop strategies to retain community members, as well as strengthen the safeguard personal information and the playfulness of activities. SNSs that launch relationship marketing activities should encourage community members to spread positive WOM through various activities. Originality/value: This study combined the commitment–trust theory and technology acceptance model. It aimed to develop a theory-based model of relationship commitment in the hospitality SNSs' context. Both trust and perceived playfulness are positively related to commitment; they are essential and important elements of successful hospitality SNSs. The gender difference plays a vital role in determining individuals' behavior intention in the hospitality SNSs, as females and males have different decision-making processes.